Exploring EFL University Students Experiences in Using Podcasts for Listening Skills - Syahril Rohim Zulfikar; Devi Mulatsih; Utut Kurniati (Al-Qalam Institue, 2026)
This study aimed to explore EFL university students’ experiences of using English podcasts as a resource for developing listening skills. A qualitative descriptive research design was employed to gain an in-depth understanding of students’ experiences, perceptions, benefits, and challenges in podcast-based listening learning. The participants were fourth-year English Education students who regularly listened to English podcasts as part of their independent learning activities. Data were collected through an open-ended questionnaire and analyzed using Braun and Clarke’s (2021) thematic analysis approach. The findings revealed four main themes: experiences of using English podcasts, the influence of podcasts on listening development, advantages and challenges of podcast use, and students’ perceptions of podcasts. Students reported that podcasts supported their listening comprehension, familiarity with different accents and speaking rates, vocabulary development, pronunciation improvement, and confidence in understanding spoken English. Although students encountered challenges related to fast speech, unfamiliar vocabulary, slang expressions, and accent variations, they developed strategies to overcome these difficulties. The findings imply that podcasts can serve as flexible and meaningful digital learning resources that promote authentic language exposure and support independent listening development among EFL learners.